2017
DOI: 10.1149/07701.0055ecst
|View full text |Cite
|
Sign up to set email alerts
|

Improving Performance and Cyclability of Printed Flexible Zinc-Air Batteries Using Carbopol Gel Electrolyte

Abstract: The formation of dendritic zinc during recharge is a critical issue hindering the widespread application of rechargeable zinc-air batteries. Here, we demonstrate that the dendritic growth of zinc can be effectively suppressed using Carbopol gel electrolyte. This work investigates the effects of the concentration of Carbopol (0-3.5 wt.%) on polarization characteristic and a discharge/recharge profile of the batteries. Moreover, the morphology of the zinc anodes and their electrochemical parameters were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A series of PVA/PAA composite electrolytes incorporated with KOH were investigated, and the highest ion conductivity reached 301 mS cm −1 at room temperature, with a weight ratio of PVA/PAA = 10/7.5 108 . Chaduang et al 109 reported that 3.5 wt% crosslinked PAA in GPEs could obviously change the anode/electrolyte interface structure, preventing the nucleation and growth of Zn dendrites and reducing the interface resistance. A PAA electrolyte neutralized by NaOH could support more than 50 times its own weight of salt solution (0.2 M Zn(CH 3 COO) 2 and 6 M KOH) at equilibrium and has been used in a variety of batteries [110][111][112] .…”
Section: Polyacrylic Acid and Its Derivativesmentioning
confidence: 99%
“…A series of PVA/PAA composite electrolytes incorporated with KOH were investigated, and the highest ion conductivity reached 301 mS cm −1 at room temperature, with a weight ratio of PVA/PAA = 10/7.5 108 . Chaduang et al 109 reported that 3.5 wt% crosslinked PAA in GPEs could obviously change the anode/electrolyte interface structure, preventing the nucleation and growth of Zn dendrites and reducing the interface resistance. A PAA electrolyte neutralized by NaOH could support more than 50 times its own weight of salt solution (0.2 M Zn(CH 3 COO) 2 and 6 M KOH) at equilibrium and has been used in a variety of batteries [110][111][112] .…”
Section: Polyacrylic Acid and Its Derivativesmentioning
confidence: 99%
“…[ 22 ] A GPE consisting of Carbopol and 8 m KOH aqueous solution was beneficial for obtaining a zinc boulder structure on the electrode surface with no dendrite formation after the first cycle. [ 135 ]…”
Section: Semisolid‐state Electrolytesmentioning
confidence: 99%
“…As ion‐conductive GPEs can also serve as a separator membrane, they can suppress Zn(OH) 4 2− crossover, which can affect the nucleation and growth of zinc and alleviate the dissolution of active materials owing to their low water contents. [ 135,136 ] A PVA–PAA–KOH GPE with bicontinuous phases was designed to integrate a 3D interconnected anion‐conducting phase with a 3D reticulated anion‐repelling phase ( Figure a). [ 137 ] This unique structure enabled the GPE to serve as a selective ion transport channel that can effectively suppressed Zn(OH) 4 2− crossover through ion repulsion (i.e., Donnan exclusion effect) by the continuous Nafion phase while slightly impairing OH − migration (predominantly by the PVA/PAA nanofiber mat).…”
Section: Semisolid‐state Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaduang et al [282] used commercial Carbopol 940 (crosslinked PAA) to highlight the improvement of discharge/recharge performance on a flexible Zinc-air battery. Likewise, Wang et al [283] develop a separator based on a paper soaked in PAA/PVA solution to enhance the battery performance.…”
Section: Zinc-airmentioning
confidence: 99%